Central Spitsbergen from sketch surveys made in 1896 and 1897 - Conway, Martin ([London] : Royal Geographical Society, 1898)
Kartta kuuluu A. E. Nordenskiöldin kokoelmaan Lisäkartat: Spitsbergen, 9 x 7,7 cm Horn Glacier, 6,7 x 8,3 cm